2015
DOI: 10.4315/0362-028x.jfp-14-431
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Diversity and Prevalence of Spoilage and Pathogenic Bacteria in Commercial Fermented Alcoholic Beverages (Beer, Fruit Wine, Refined Rice Wine, and Yakju)

Abstract: The present study examined 469 commercially available fermented alcoholic beverages (FABs), including beer (draft, microbrewed, and pasteurized), fruit wine (grape and others), refined rice wine, and yakju (raw and pasteurized). Samples were screened for Escherichia coli and eight foodborne pathogens (Bacillus cereus, Campylobacter jejuni, Clostridium perfringens, Escherichia coli O157:H7, Listeria monocytogenes, Salmonella spp., Staphylococcus aureus, and Yersinia enterocolitica), and the aerobic plate count,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…Fermented foods that contain appreciable levels of fermentationproduced organic acids (>100 mM), combined with low water activity, salt, nitrite and other antimicrobials, have a long record of food safety 78 . Likewise, beverages containing 4% or more alcohol and pH values less than 4.5 are also considered microbiologically safe 79 . Many LAB, whether part of the autochthonous microbiota or added as starter cultures, are known to produce bacteriocins that inhibit undesirable bacteria, including Listeria, Staphylococcus and Clostridium 80 .…”
Section: Fermentation and Food Safety Does Fermentation Improve Food mentioning
confidence: 99%
“…Fermented foods that contain appreciable levels of fermentationproduced organic acids (>100 mM), combined with low water activity, salt, nitrite and other antimicrobials, have a long record of food safety 78 . Likewise, beverages containing 4% or more alcohol and pH values less than 4.5 are also considered microbiologically safe 79 . Many LAB, whether part of the autochthonous microbiota or added as starter cultures, are known to produce bacteriocins that inhibit undesirable bacteria, including Listeria, Staphylococcus and Clostridium 80 .…”
Section: Fermentation and Food Safety Does Fermentation Improve Food mentioning
confidence: 99%
“…All microbiological analyses were performed according to the US Food and Drug Administration Bacteriological Analytical Manual (USFDA 2011) and the Korea Food Code (MFDS 2012), with some modifications as described previously (Choi et al 2014;Jeon et al 2015).…”
Section: Quantitative Microbiological Analysis (Bacterial Enumeration)mentioning
confidence: 99%
“…To place the results of the present study in proper perspective, selected reported studies on the contamination of raw and processed rice products by B. cereus are being briefly mentioned. These include Korean raw rice affected by production area and degree of milling (Kim et al, ); Korean rice during storage (Zhang et al, ); cooked rice (Dong, ; Hariram & Labbé, ; Jawad & Mutalib, ; Jawad, Mutalib, & Abdullah, ; Rachtanapun, Tantala, Klinmalai, & Ratanasumawong, ; Wang, Ding, & Oh, ); fried rice (Jawad, Mutalib, & Abdullah, ); rice cake (Wang, Park, Choi, Ha, & Oh, ); and refined and turbid rice wines (Jeon et al, ; Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%